Empowering Women Through Contraceptive Education Makes Responsible Family Decisions A Reality - Kasim, Jamila; Hasifah, Hasifah; A, Alfiah; Kadrianti, Erna; Jamaluddin, Maryam (Room of Civil Society Development, 2024)
Empowering women through contraceptive education is an effort to provide knowledge, skills and access to various contraceptive methods to women to provide control to women regarding decisions regarding their reproductive health. The aim of community service is to increase the knowledge of women of childbearing age regarding appropriate contraceptive knowledge. with health conditions in Taraweang village in the form of counseling by providing material about types of contraceptives, disadvantages and advantages and side effects, the activity method is by distributing leaflets to participants then conducting counseling and evaluating using a pre-post test questionnaire. The results of activities regarding contraception were an increase in the knowledge of women of childbearing age. Where the knowledge of women of childbearing age before good knowledge education was 22%, and after good knowledge counseling it was 81%. Providing contraceptive knowledge to women of childbearing age has a positive social and health impact, giving them greater control over their bodies and reproductive lives.